Ultra-low Output Impedance RF Power Amplifier for Parallel Excitation - Chu, Xu (2009)
Inductive coupling between coil elements of a transmit array is one of the key challenges that parallel RF transmission faces. An ultra-low output impedance RF power amplifier concept was introduced to address this challenge. In an example implementation, an output-matching network was designed to transform the drain-source impedance of the MOSFET into a very low value for suppressing inter-element coupling effect, and meanwhile, to match the input impedance of the coil to the optimum load of the MOSFET for maximizing the available output power. Two prototype amplifiers with 500W output rating were developed accordingly, and were further evaluated with a transmit array in phantom experiments. Compared to the conventional 50Ω sources, the new approach exhibited considerable effectiveness suppressing the effects of inter-element coupling. The experiments further indicated that the isolation performance was comparable to that achieved by optimized overlap decoupling. The new approach, benefiting from a distinctive current-source characteristic, also exhibited a superior robustness against load variation. Feasibility of the new approach in high field MR was demonstrated on a 3T clinical scanner.